Folk Christian Community pada Jemaat Kristen di Gereja Kalimantan Evangelis (GKE) Resort Pendahara Katingan - Stynie Nova Tumbol; Yane Octavia Rismawati Wainarisi (Asosiasi Teolog Indonesia, 2023)
The cultural openness of Dayak society in Central Borneo has enabled the Dayak people to quickly adopt Christian traditions since Christianity came there in the late 1830s. However, not all Christian communities were able to reconcile their faith with their indigenous culture. Many Dayak continue to face the dilemma of living as “true” Christians abandoning all indigenous traditions yet burdened by the extinction of indigenous culture or, on the other hand, living as Christians continuing to observe local traditions while being absorbed in syncretist practices. Katingan Regency is distinctive for the number of Christian communities that continue in adherence to their original religion of Kaharingan. More than religious affiliation, Kaharingan is itself a cultural aspect of the Dayak people in Central Borneo. This qualitative research uses phenomenological methods to study GKE Resort Pendahara Katingan, whose congregations remains actively involved in the practice of Kaharingan ancestral rituals and traditions. Data were collected through direct observations, interviews, and document research, which were then triangulated prior to analysis and final conclusions. Findings of the study suggest that not all indigenous cultures stemming from folk religion are bad in principle, since many of these promote ethical values including ecosystem preservation within the framework of ecotheology. Such localized ethical wisdom supports and aligns with church traditions, as seen in the notion of belom bahadat—a term denoting the upright, virtuous life informed by the truth of tradition—that bespeaks hospitality towards fellow creatures as well as the earth where humanity dwells.